Nurses' perceptions of caring activities in nursing - Neriman Akansel; Roger Watson; Nursel Vatansever; Aysel Özdemir (Wiley, 2021)
Abstract Aim This study aimed to determine nurses' perceptions of caring activities in nursing. Design A descriptive study design. Methods A Turkish translation of the 25‐item version of the Caring Dimensions Inventory was completed by 260 nurses working in one university hospital. Data were analysed using Mokken scaling. Results Technical aspects of nursing were highly endorsed items such as "observing the effects of a medication on a patient, measuring vital signs, being technically competent with a clinical procedure, consulting with the doctor" except for the item "providing privacy for a patient" which is a psychosocial item. The range of items included in the Mokken scale with "providing privacy for a patient" (mean = 4.31) as the most endorsed, and "exploring the patient's lifestyle" (mean = 2.60) being the least endorsed item. Listening to patients and involving them in their care are not considered as caring.